Changes in transcript levels of starch hydrolysis genes and raising citric acid production via carbon ion irradiation mutagenesis of Aspergillus niger - Hu, Wei (PLoS One, 2017)
The filamentous ascomycete Aspergillus niger is well known for its ability to accumulate citric acid for the hydrolysis of starchy materials. To improve citric acid productivity, heavy ion beam mutagenesis was utilized to produce mutant A.niger strains with enhanced production of citric acid in this work. It was demonstrated that a mutant HW2 with high concentration of citric acid was isolated after carbon ion irradiation with the energy of 80Mev/μ, which was obvious increase higher than the original strain from liquefied corn starch as a feedstock. More importantly, with the evidence from the expression profiles of key genes and enzyme activity involved in the starch hydrolysis process between original strain and various phenotype mutants, our results confirmed that different transcript levels of key genes involving in starch hydrolysis process between original strain and mutants could be a significant contributor to different citric acid concentration in A.niger, such as, amyR and glaA, which therefore opened a new avenue for constructing genetically engineered A.niger mutants for high-yield citric acid accumulation in the future. As such, this work demonstrated that heavy ion beam mutagenesis presented an efficient alternative strategy to be developed to generate various phenotype microbe species mutants for functional genes research.